KARAKTERISTIK PEROKOK DI KALANGAN CIVITAS AKADEMIKA FAKULTAS HUKUM UNIVERSITAS ANDALAS - Muhammad Raihan; Fenty Anggrainy; Yuniar Lestari; Miftah Irramah; Yessy Susanty Sabri; Zurayya Fadila (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The number of smokers increases every year. It becomes the focus of the Indonesian government’s attention. Through the healthy campus program, the Indonesian Ministry of Health designated Andalas University as one of the pilot campuses, but there are still smokers on campus. Itsn’t just students who smoke, but lecturers and education staff as well. To determine the characteristics of smokers among the academic civility in Faculty of Law, Andalas University. The method used is descriptive observational with quota sampling technique. The sample consisted of 323 students, 18 lecturers, and 5 staff. Data were collected by questionnaire and analyzed with computerized program. The research results showed that 28.9% of the academic civility at Faculty of Law, Andalas University were smokers. The typical average age is 22 years, dominated by men, in general they also have families who smoke. The highest age for starting smoking is 16 years or older. Smokers are dominated by light smokers. The most commonly consumed type of cigarettes is white cigarettes, but 9.5% also use e-cigarettes. The driving force behind smoking behavior usually the social environment. The level of knowledge of academic civility is sufficient category. The conclusion obtained is that there are still smokers among the academic community, so preventive efforts should be made to reduce the number of smokers on campus.